Answer:
Step-by-step explanation:
Given : Expression ![V = (x)(4x+3)(4x)](https://tex.z-dn.net/?f=V%20%3D%20%28x%29%284x%2B3%29%284x%29)
To find : Suppose you multiplied the cereal box dimensions in a different order ?
Solution :
The given expression is the product of three numbers,
First we multiply first two terms,
![(x)(4x+3)=4x^2+3x](https://tex.z-dn.net/?f=%28x%29%284x%2B3%29%3D4x%5E2%2B3x)
Substitute back,
![V = (4x^2+3x)(4x)](https://tex.z-dn.net/?f=V%20%3D%20%284x%5E2%2B3x%29%284x%29)
Then multiply the left terms,
![V =16x^2+12x](https://tex.z-dn.net/?f=V%20%3D16x%5E2%2B12x)
Therefore, ![V=(x)(4x+3)(4x)=16x^2+12x](https://tex.z-dn.net/?f=V%3D%28x%29%284x%2B3%29%284x%29%3D16x%5E2%2B12x)